2009
DOI: 10.1002/ijc.24641
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of myosin Va by Snail is involved in cancer cell migration and metastasis

Abstract: Cell migration, which involves acto-myosin dynamics, cell adhesion, membrane trafficking and signal transduction, is a prerequisite for cancer cell metastasis. Here, we report that an actin-dependent molecular motor, unconventional myosin Va, is involved in this process and implicated in cancer metastasis. The mRNA expression of myosin Va is increased in a number of highly metastatic cancer cell lines and metastatic colorectal cancer tissues. Suppressing the expression of myosin Va by lentivirus-based RNA inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 38 publications
1
74
0
5
Order By: Relevance
“…Electrophoretic mobility shift assay (EMSA) was performed using the LightShift chemilluminescent EMSA kit (Pierce, Rockford, IL) essentially the same as described 63 . The double-stranded oligonucleotide used as a probe for EMSA corresponds to the following sequence in the putative PBX3 WT binding site of the CACNA2D1 promoter region, 5 0 -TCCTCCCTGAT TTATTCCCCCG-3 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic mobility shift assay (EMSA) was performed using the LightShift chemilluminescent EMSA kit (Pierce, Rockford, IL) essentially the same as described 63 . The double-stranded oligonucleotide used as a probe for EMSA corresponds to the following sequence in the putative PBX3 WT binding site of the CACNA2D1 promoter region, 5 0 -TCCTCCCTGAT TTATTCCCCCG-3 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Snail is known to act as a transcriptional repressor; very few reports, however, have shown that Snail activates target genes, with the exception of the direct activation of myosin Va by Snail (35). Here, we showed that the SNAG domain of Snail is responsible for the promotion of ERCC1 transcription.…”
Section: Discussionmentioning
confidence: 53%
“…Multiple functions have been assigned to this actin-dependent molecular motor, including the transport of melanosomes, smooth endoplasmic reticulum, recycling endosomes, neurotransmitter vesicles, mRNA (Reck-Peterson et al 2000, Langford 2002, Salerno et al 2008, and neuroendocrine vesicles (Rudolf et al 2003). A role for MYO5A in tumor cell migration, invasion, and metastasis has recently been described (Du et al 2007, Lan et al 2010. Thus, our finding that MYO5A gene and protein expression is Endocrine-Related Cancer (2010) 17 361-371…”
Section: Discussionmentioning
confidence: 70%